Management of Pilonidal Sinus in Manipal Teaching Hospital: A Cross-sectional Study - Shrestha, Binod Bade; Shrestha, Sujan; Mishra, Sushil; Shrestha, Sudarsan (Nepal Journal of Medical Sciences, 2024)
Introduction: The study aimed to assess the effectiveness of various surgical treatments for pilonidal sinus, including excision with primary closure, endoscopic pilonidal sinus treatment (EPSiT) and rhomboid flap reconstruction. Methods: This cross-sectional study was conducted in Department of General Surgery, Manipal College of Medical Sciences, Pokhara, Nepal, from March 2020 to January 2023, following institutional review board approval (Reference number: MEMG/IRC/504/GA) and obtaining written informed consent. Patients of all genders and ages diagnosed with pilonidal sinus were included. Data were analyzed using SPSS version 25.0, with results presented as mean ± SD, frequency, and percentage. A p-value ≤ 0.05 was deemed statistically significant. Results: The study included 67 participants, with 49 males (73.1%) and 18 females (29.6%), averaging 23.61±6.87 years in age. Thirty-one patients (46.2%) underwent rhomboid flap surgery, 30 (44.8%) patients underwent EPSiT, 6 (9%) patients had excision with primary repair. Complications were seen in 17 patients (25.37%), including surgical site infections (16.4%), recurrence (7.5%), and dehiscence (1.5%). Average hospital stay was 4.07±3.51 days, surgery duration was 51.61±17.91 minutes, and drain removal occurred at 4.72±3.98 days. Surgery duration was comparable in EPSiT and excision with primary repair (p=0.08) whereas it was significantly less when compared to rhomboid flap (p=0.00). Hospital stay and drain duration were significantly less in EPSiT when compared to the other two treatment modalities. The complications were similar across the three treatments. Conclusions: EPSiT had shorter duration of hospital stay and drain days than rhomboid flap reconstruction or primary closure. The complications were similar across various treatment modalities.